2004
DOI: 10.1197/j.aem.2004.02.528
|View full text |Cite
|
Sign up to set email alerts
|

Basic Cardiac Life Support Providers Checking the Carotid Pulse: Performance, Degree of Conviction, and Influencing Factors

Abstract: The American Heart Association recently abolished the carotid pulse check during cardiopulmonary resuscitation for lay rescuers, but not for health care providers. Objectives: The aim of the study was to evaluate health care providers' performance, degree of conviction, and influencing factors in checking the carotid pulse. Methods: Sixtyfour health care providers were asked to check the carotid pulse for 10 or 30 seconds on a computerized mannequin simulating three levels of pulse strength (normal, weak, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…There have been 9 LOE D5 studies demonstrating that both lay rescuers 24 -26 and healthcare providers [27][28][29][30][31][32] have difficulty mastering the pulse check and remembering how to perform it. Three LOE D5 studies support the ability of healthcare providers to perform the pulse check; 2 evaluated the direct ear-to-chest method in infants, 33,34 and the third supported an alternative technique for the carotid pulse check when tested by dental students on healthy volunteers.…”
Section: Pulse Checkmentioning
confidence: 99%
“…There have been 9 LOE D5 studies demonstrating that both lay rescuers 24 -26 and healthcare providers [27][28][29][30][31][32] have difficulty mastering the pulse check and remembering how to perform it. Three LOE D5 studies support the ability of healthcare providers to perform the pulse check; 2 evaluated the direct ear-to-chest method in infants, 33,34 and the third supported an alternative technique for the carotid pulse check when tested by dental students on healthy volunteers.…”
Section: Pulse Checkmentioning
confidence: 99%
“…Studies have shown that both laypersons and healthcare providers have difficulty detecting a pulse. [35][36][37][38][39][40][41][42][43][44] For this reason pulse check was deleted from training for lay rescuers several years ago, and is deemphasized in training for healthcare providers. The lay rescuer should assume that cardiac arrest is present and should begin CPR if an adult suddenly collapses or an unresponsive victim is not breathing or not breathing normally (ie, only gasping).…”
Section: Recognition Of Arrest (Box 1)mentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44] Healthcare providers also may take too long to check for a pulse. 38,41 • The lay rescuer should not check for a pulse and should assume that cardiac arrest is present if an adult suddenly collapses or an unresponsive victim is not breathing normally.…”
Section: Pulse Checkmentioning
confidence: 99%
“…The authors stated, If the absence of a pulse was the only factor determining the onset of CPR maneuvers, approximately 50% of pulseless patients simulated in our study would not have had CPR initiated. 47 …”
Section: Importance Of Vital Signs and Movement During Vt/vfmentioning
confidence: 99%